PEMANFAATAN LAHAN TADAH HUJAN MELALUI PEMBERIAN PUPUK HAYATI PADA BERBAGAI VARIETAS BAWANG MERAH (Allium ascalonicum L.) DI SUMATERA SELATAN - Hawayanti, Erni; Aminah, R. Iin Siti (Universitas Muhammadiyah Palembang, 2017)
This research aims to know and get the kind of biological fertilizer is best against the growth and production of some plant varieties of union (Allium ascalonicum L.) on wetland rainwater. This research has been carried out in the land of farmers in the village of tugu sub-district Lempuing Jaya regency of Ogan Komering Ilir, South Sumatera Province from May until July 2017. This study used Randomize Design Group (RAK) Factorial combination treatment with 9 reply repeated 3 times and example of five plants per treatment. As the type of biological Fertilizer treatment factor (H) consisting of H1 = Biological liquid Fertilizer, H2 = Fertilizer Mycorrizha and varieties union (V) consist of V1 = Bima Gajah V2 = Bima Brebes V3 = Pancasona. The variable of observed was 1. Plant height (cm) 2. The number of leaves (blades) 3. Harvest age (hst) 4. The number of tubers per clump (clopes) 5. Fresh weight per clump (g) weight per tuber plots. Based on the result of the study showed the treatment of this type of biological fertilizer effect until very real for all variable. Treatment of varieties and the interaction effect was evident against variable number of bulbs, tuber weight per clump. Weight per tuber plots and not real against other variable. In tabulating the fertilizer treatment combination of mycorrizha and varieties of tuber weight per yield the best swat with an Average that was 2493.77 g/swath or equivalent of 9,98 ton/ha onion.